Transforming Islamic Boarding School as Indonesian of Islamic Educational Institution in the Digital Era - Mansir, Firman; Karim, Abdul; Tumin; Purnomo, Halim (International Journal of Psychosocial Rehabilitation, 2020)
This research studies the dynamics of an Islamic boarding school as a society-based Islamic education institution in Indonesia. Islamic boarding school as the oldest education institution intends to provide proof that its contribution to Indonesian Islamic education is very large. Thus, the Islamic boarding school that was previously known as old-fashioned, old, and outdated institutions is now changing with a variety of modern appearances. This research was qualitative research sourced from the field with case studies in Indonesia. The procedure for obtaining data were interviews, observation, and documentation. This research proved that the dynamics of Islamic boarding schools in the digital era experienced a process of rapid changes in policy from the government and changes in the times themselves, that did not make Islamic educational institutions fall and die. However, Islamic boarding schools still can survive amid various technological advancements and changing times. This research can be used as a scientific reference in viewing the Islamic boarding school map in Indonesia. Thus, sources of educational institutions can be constantly updated. Therefore, Islamic boarding schools known as the oldest Islamic education institution can become excellent institutions in the face of the digital era, and in the end, they become the leading educational institutions.